2015
DOI: 10.1007/s11046-015-9907-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute Invasive Pulmonary Aspergillosis Complicating Allergic Bronchopulmonary Aspergillosis: Case Report and Systematic Review

Abstract: Aspergillus fumigatus can cause a variety of pulmonary syndromes including allergic bronchopulmonary aspergillosis (ABPA), chronic pulmonary aspergillosis and invasive pulmonary aspergillosis (IPA). Occurrence of IPA and ABPA in the same patient is rare as the risk factors for ABPA and IPA are different. We describe a 45-year-old male with ABPA treated with oral methylprednisolone and itraconazole, who developed acute respiratory failure secondary to IPA, a month later. The patient subsequently improved after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 24 publications
(27 reference statements)
1
12
0
Order By: Relevance
“…In fact, one male patient with ABPM in our hospital developed chronic progressive pulmonary aspergillosis during his clinical course. Other patients who have developed invasive pulmonary aspergillosis and chronic progressive pulmonary aspergillosis under SCSs have also been reported . Nineteen of our 25 patients who did not receive SCSs as an initial treatment improved, and we found that each treatment option without SCSs was effective at various different frequencies.…”
Section: Discussionsupporting
confidence: 52%
“…In fact, one male patient with ABPM in our hospital developed chronic progressive pulmonary aspergillosis during his clinical course. Other patients who have developed invasive pulmonary aspergillosis and chronic progressive pulmonary aspergillosis under SCSs have also been reported . Nineteen of our 25 patients who did not receive SCSs as an initial treatment improved, and we found that each treatment option without SCSs was effective at various different frequencies.…”
Section: Discussionsupporting
confidence: 52%
“…Based on the results of antifungal susceptibility testing, we expected several anti-fungal agents to be ineffective against the pathogen. It has been reported that ABPA can progress into invasive pulmonary aspergillosis ( 15 ). Sometimes corticosteroid therapy results in compromised immunity and fungal dissemination, as a result, we determined that anti-fungal therapy might not be effective in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Nine cases of invasive aspergillosis have been reported in patients with ABPA. [ 5 ] A probable increase in serum steroid levels secondary to cytochrome enzyme inhibition consequent to itraconazole use has been postulated.…”
Section: Discussionmentioning
confidence: 99%